Cost and potential of carbon abatement from the UK perennial energy crop market. Issue 2 (29th November 2013) - Alexander, Peter; Moran, Dominic; Rounsevell, Mark D. A.; Hillier, Jonathan; Smith, Pete
Abstract Biomass produced from perennial energy crops is expected to contribute to UK renewable energy targets, reducing the carbon intensity of energy production. The UK government has had incentive policies in place targeting both farmers and power plant investors to develop this market, but growth has been slower than anticipated. Market expansion requires the interaction of farmers growing these crops, with the construction of biomass power plants or other facilities to consume them. This study uses an agent‐based model to investigate behaviour of the UK energy crop market and examines the cost of emission abatement that the market might provide. The model is run for various policy scenarios attempting to answer the following questions: Do existing policies for perennial energy crops provide a cost‐effective mechanism in stimulating the market to achieve emissions abatement? What are the relative benefits of providing incentives to farmers or energy producers? What are the trade‐offs between increased or decreased subsidy levels and the rate and level of market uptake, and hence carbon abatement? The results suggest that maintaining the energy crop scheme, which provides farmers' establishment grants, can increase both the emissions abatement potential and cost‐effectiveness. A minimum carbon equivalent abatement cost is seen at intermediate subsidy levels for energy generation. This suggests that there is an optimum level that cost‐effectively stimulates the market to achieve emissions reduction.